2011
DOI: 10.1103/physrevb.84.205412
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the band gap and magnetic properties of BN sheets impregnated with graphene flakes

Abstract: The BN sheet is a nonmagnetic wide-band-gap semiconductor. Using density functional theory, we show that these properties can be fundamentally altered by embedding graphene flakes. Not only do graphene flakes preserve the two-dimensional (2D) planar structure of the BN sheet, but by controlling their shape and size, unexpected electronic and magnetic properties also emerge. The electronic band structure can be tuned from a direct gap to an indirect gap, the energy gap can be further modulated by changing the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 28 publications
3
69
0
Order By: Relevance
“…35,36 It is recently shown that the details of the bonding at the h-BN/graphene interface can change the type of intrinsic doping of the system. 37 Just to name a few other examples of how this chemical and structural diversity in this low dimensional hybrid system enable control over magnetic properties; zigzag-edges in ribbons have been suggested to lead to ferromagnetic behavior 38 while more complex interfaces, like those present in h-BN clusters embedded in graphene, can be antiferromagnetic 39 may also be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 It is recently shown that the details of the bonding at the h-BN/graphene interface can change the type of intrinsic doping of the system. 37 Just to name a few other examples of how this chemical and structural diversity in this low dimensional hybrid system enable control over magnetic properties; zigzag-edges in ribbons have been suggested to lead to ferromagnetic behavior 38 while more complex interfaces, like those present in h-BN clusters embedded in graphene, can be antiferromagnetic 39 may also be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…In recent experiments, co-deposition of graphene and h-BN was attempted to form hybridized h-BNC besides synthesizing atomic layers of h-BNC by substituting C atoms in graphene layer with B and N atoms. The significance of the chemical and electrical tunability achieved in these experimental methods motivated using PECVD to synthesize several other members of h-BN derivatives [23,[26][27][28][29].…”
Section: Other Hybrid 2d-monolayersmentioning
confidence: 99%
“…The h-BN monolayers embedded with triangular graphene flakes can modify the electronic properties as well as the magnetic properties [34,37]. The magnetic moments of the graphene-like flake embedded h-BN monolayer can be controlled depending on the number of the substituted C atoms in the h-BN monolayers (Figure 4), where and are the numbers of the B atoms and the N atoms replaced with the C atoms and positive and negative ( − ) values are used for the T1-C C and T2-C C structures, respectively.…”
Section: Carbon Flakementioning
confidence: 99%
“…The atomic vacancies in h-BN layers can be introduced using electron beam irradiations and are shown to be useful as a source of magnetism [10,[24][25][26][27]. The introductions of C atoms and graphene-like flakes into h-BN sheets have been also performed via electron beam irradiations due to analogous structural properties among B, C, and N elements [28][29][30][31][32][33][34][35][36], which can tune the electronic and the magnetic properties [37][38][39]. It is predicted theoretically that the energy band gaps are tunable depending on the size of the graphene flakes [37,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation